(untitled) (Medical Forum Monthly, 2023)
Objective: The purpose of this study was to evaluate and compare the efficacy of oral lycopene with intralesional steroid injection and in combination. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Department of Oral and Maxillofacial Surgery (Surgical Unit 2), NID, Multan from May 2021 to February 2022. Materials and Methods: Total 45 patients of OSF participated; three groups each containing 15 subjects were formed. Oral lycopene on daily basis was given to subjects in Group I, biweekly intralesional triamcinolone (40 mg/ml) was administered in participants of Group II and Group III received combination (biweekly steroid injection and daily lycopene) for a period of three months. Any increase in mouth opening and decrease in burning sensation of oral mucosa was noted monthly. Results: Most of the participants in our study 60% were young male adults and 40% were females participated in our study also comes under the category of young adults. Therefore, the mean age of the subjects in this study was 27.9±3.1 years. There was significant increase in mouth opening in all groups with p≤0.04. Group III showed relatively increased mouth opening followed by group II and III. We noticed almost complete relief of burning sensation in subjects of all three groups, rapid decline in the burning sensation was observed in group I. Conclusion: Combination of oral lycopene with steroid injection is more effective in minimizing the symptoms of OSF